Material characterization model using rectangular resonator waveguide - Mohamad Shaiful, Abdul Karim; Ahmad Afif, Mohd Faudzi; Nurhafizah, Abu Talip @ Yusof; Khatun, Sabira
Circular cylindrical resonator has been widely used for the purpose of material characterization where the complex permittivity of the material is evaluated. However, the design of circular cylindrical resonator is not a preferable design, as it needs a precise sampling preparation so the sample fits the cavity of the resonator. Precise sample preparation is needed in order to reduce air gap between the sample and the walls of the cavity. Air gap may cause degradation of accuracy of the sample valuation. Moreover, mostly common resonator only capable in measuring low-loss materials. The proposed rectangular resonator design is much more convenient and easy to handle, as it does not require a complex sample preparation. Samples can be in any shape or in other word, arbitrarily shape. The proposed design also has the capability in measuring low-loss and high-loss sample by varying the windows of the cavity.